2011
DOI: 10.1007/s12224-011-9100-2
|View full text |Cite
|
Sign up to set email alerts
|

Nomenclatural Revision for the Order Scorzonero-Chrysopogonetalia

Abstract: The order Scorzonero-Chrysopogonetalia describes the dry grasslands of a large area in southeastern Europe, centred around and east of the Adriatic Sea (i.e., ). Most commonly, Scorzonero-Chrysopogonetalia is arranged within the classes Festuco-Brometea or Brachypodio-Chrysopogonetea or it is split into two orders classified within Festuco-Brometea and Thero-Brachypodietea; according to other minor opinions, the order is sometimes assigned to Brachypodio-Brometea, TheroBrachypodietea or Ononido-Rosmarinetea. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…This study revealed that even in a small area, bryophyte flora displays a biogeographical pattern which is in accordance with a biogeography based on vascular plants (Horvat et al, 1974;Šugar, 1984;Kaligarič, 1997;Terzi, 2011). However, the view is more general since bryophytes commonly show broader areas of distribution than vascular plants and lack local endemics (Frahm, 2001).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This study revealed that even in a small area, bryophyte flora displays a biogeographical pattern which is in accordance with a biogeography based on vascular plants (Horvat et al, 1974;Šugar, 1984;Kaligarič, 1997;Terzi, 2011). However, the view is more general since bryophytes commonly show broader areas of distribution than vascular plants and lack local endemics (Frahm, 2001).…”
Section: Resultssupporting
confidence: 85%
“…The grasslands of the area are seminatural, belonging to the Amphiadriatic dry steppic sub-Mediterranean grasslands of the Prealpine, Illyrian and Dinaric regions (Scorzoneretalia villosae Kovačević 1959), represented by meadows (Scorzonerion villosae Horvatić ex Kovačević 1959) and rocky pastures (Chrysopogono grylli-Koelerion splendentis Horvatić 1973 and Saturejion subspicatae Tomić-Stanković 1970) (Horvat et. al., 1974;Šugar, 1984;Kaligarič, 1997;Terzi, 2011;Mucina et al, 2016;Škvorc et al, 2017). Apart from these main vegetation formations however, many other habitats like arable fields, vineyards, olivegroves, orchards, paths, ponds, rocks, stone-pits, dolines and drystone walls are present in the area.…”
Section: Study Areamentioning
confidence: 99%
“…Dengler 2003, 2004, Dengler et al 2003, Mucina et al 2009, Terzi 2011, Di Pietro 2011, Biondi & galdenzi 2012, Becker et al 2012. In this work we use the name Brometalia erecti Koch 1926 according to Biondi & galdenzi (2012), waiting for a definitive sentence of the ICPN nomenclature Committee (Weber et al 2000) about its rejection and substitution by Brachypodietalia pinnati Korneck 1974, as suggested by Dengler et al (2003) and Mucina et al (2009 …”
Section: Notes On the Attribution To Higher Syntaxonomical Unitsmentioning
confidence: 99%
“…In the last two decades several papers were devoted to the syntaxonomical problems of these communities in Europe (see Royer 1991;Mucina & Kolbek 1993, Dengler et al 2003, Dengler 2004, Chytrý et al 2007, Mucina et al 2009, Terzi 2011, including Italy, with particular concern on the peninsular regions (Biondi et al 1995, 2005, Di Pietro 2011, Biondi & galdenzi 2012. Based on the afore mentioned literature data about Italy, some considerations raised: i) much of the information on this vegetation type consists in local contributions mainly focused on the limestone substrata of central and southern Apennines; ii) very few studies have been carried out in the north-western Apennines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We also welcome contributions focusing on phytosociological nomenclature, provided they are of relevance for a broader international audience. Outstanding examples of this kind of studies are rare -perhaps due to the lack of attractive publication venues -but the thorough nomenclatural revision of a whole phytosociological order by Terzi (2011) could serve as a model for the manuscripts that we would like to accommodate in the new "Phytosociological Nomenclature" section. This section is also open to the discussion of different interpretations of the nomenclatural rules (e.g.…”
Section: Types Of Papers We Would Like To See In Phytocoenologiamentioning
confidence: 99%